THE ROLE OF CYTOKINE NETWORK IN HEPATOCELLULAR DAMAGE CAUSED BY СHRONIC HEPATITIS C - L. Ph. Skljar (Медицинская иммунология)
Abstract. Hepatitis C virus (HCV) is the leading cause of chronic hepatitis, liver cirrhosis and hepatocellular carcinoma. Liver damage in chronic viral hepatitis C is caused by both direct cytopathic viral effects, and indirect immune-mediated mechanisms. The cytokines locally produced in the liver, as well as those circulating in the blood circulation, play an important role in the control of viral replication and sufficiently contribute to hepatocellular damage. The goal of present study was to investigate the contents of some cytokines in blood serum and their local levels, being in interrelation with indices of necrotic inflammatory changes in the liver tissue. Correlations established between systemic and local contents of studied cytokines, and morphological indices indicate that, among immunological tests checked, the contents of IL-4, IL-10, IL-12p70, and TNFα in blood serum and supernatants of liver biopsies were of the greatest significance for determining the stage of fibrosis. Quantitative assays of abovementioned cytokines in blood serum represent, therefore, an alternative approach in order to perform noninvasive screening of liver fibrosis.